PENGARUH DEBT TO EQUITY RATIO, NET PROFIT MARGIN DAN TOTAL ASSET TURNOVER TERHADAP PERTUMBUHAN LABA PADA PT BUKIT ASAM TBK PERIODE 2009 – 2023 - Lilis Muhlisoh; Arif Hidayat (Journal of Research and Publication Innovation, 2024)
This study aims to determine the influence of Debt to Equity Ratio, Net Profit Margin and Total Asset Turnover on Profit Growth at PT Bukit Asam Tbk for the 2009-2023 Period. The research method used is a quantitative method using secondary data from the financial profession of PT Bukit Asam Tbk for the 2009-2023 period. In this study, the data analysis used was descriptive statistics, classical asusmsi test, multiple linear regression, hypothesis test (t test and f test) and determination coesphiciency. The results of this study prove that partially (t) Debt to Equity Ratio has no effect on Profit Growth which is shown by the t-value of 1,624 < ttable 2,201 and the significance value of 0,133 > 0.05. Net Profit Margin has a significant effect on Profit Growth which is shown by the t-value of 3,533 > ttable 2,201 and a significance value of 0,005 < 0,05. Total Asset Turnover did not have a significant effect on Profit Growth which was shown by a t-value of -2,065 < ttable 2,201 and a significance value of 0,063 > 0,05. From this study simultaneously (f) shows that Debt to Equity Ratio, Net Profit Margin and Total Asset Turnover together have a significant effect on Profit Growth at PT Bukit Asam Tbk for the 2009-2023 Period which is shown by the value of f-value > ftable (4,337 > 3,59) and strengthened with a significance value of 0,030 < 0,05. The result of the determination coefficient was 41,7%, which means that the dependent variabel can be explained by independent variabels, while the remaining 58,3% is influenced by other factors that were not tested in this study.